CYTOTOXIC ISOFLAVONOIDS OF PACHYRRHiUS EROSUS SEEDS - Leonardus B.S. Kardono; Soefjan Tsauri; John M. Pezzuto; A. Douglas Kinghorn; Kosasih Padmawinata (Research Center for Chemistry - LIPI, 1994)
By bioactivity-directed fractionation, phytochemical and cytotoxic studies of the seeds of Pachyrrhizus erosus L. resulted in the isolation of isoflavonoid-based compounds, one novel compound and eight known compounds, comprising the novel coumaronochromene, pachyrrhisomene 1, the known pterocarpan, neodulin 2, the known 3-arylcoumarin, pachyrrhizin 3, the known isoflavonoid, dehydroneotenone 4, five known rotenoids, rotenone 5, l2a-hydroxyrotenone 6, 12a-hydroxypachyrrhizone 7, 12a-hydroxyerosone 8, and 12a-hydroxymunduserone 9. The identities of these compounds were elucidated or confirmed using combination of modern one- and two- dimensional NMR techniques, such as 1H-1H COSY, CSCMID, 1H-1H NOESY, and selective INEPT, as well as by comparison with published spectroscopic data. It is likely that the novel compound, pachyrrhisomene 1 is derived from the same biosynthetic intermediate as the pterocarpan, neodulin 2. All of these compounds were evaluated for their anticancer potential in a battery of tumour cell lines, comprishing P-388 lymphocytic leukemia, KB-carcinoma of the nasopharynx, a multi-drug resistant variant of KB, KB-VI, and a number of human cancer cell lines derived from a variety of tumour types, namely fibrosarcoma, lung, colon, melanoma, and breast. Two compounds, rotenone 5 and 12a-hydroxyrotenone 6 were observed to exhibit potent but nonspecific activity.